Dupilumab treatment for Chinese Nagashima-type palmoplantar keratoderma associated with atopic dermatitis: a case report - Hua, Chunting; Cheng, Hao; Chen, Xianzhen (Frontiers in Immunology, 2025)
Patients with Nagashima-type palmoplantar keratoderma (NPPK) experience progressive, painful hyperkeratosis and fissuring of palms and soles that limits daily activities Due to the incomplete understanding of its pathogenesis, there are currently no effective treatments for NPPK. We report a 26-year-old woman with lifelong, worsening palmoplantar keratoderma, nail dystrophy, and concomitant atopic dermatitis refractory to topical treatments. Next-generation sequencing revealed compound heterozygous mutations in SERPINB7 (c.796C>T, p.Arg266Ter) and filaggrin (FLG, c.3321delA, p.Gly1109GlufsTer13), while her asymptomatic parents and brother carried only single heterozygous variants, underscoring the digenic pathogenesis in our patient. After 42 weeks of dupilumab treatment, palmoplantar keratosis and nail changes had almost completely resolved, and the eruption resembled mild chronic eczema. Dupilumab therefore appears to be a safe and effective option for digenic NPPK complicated by atopic dermatitis and warrants further investigation in larger cohorts.